2012
DOI: 10.5402/2012/103715
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Aspects of the Corrosivity of Simulated Soil Solutions

Abstract: Corrosion of buried steel pipe is a permanent engineering problem and, albeit the counter measures against degradation, when the corrosion process takes place, the damage has costly impact. In order to study the corrosion behavior of pipelines, it is possible to use actual soil extracts or simulated soil solutions. The extract is much related to specific sites and consequently too strict to permit a general understanding. The simulated soil presents, as advantage, its inorganic characteristic and easy preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…With the increase of corrosion, hydrogen bubbles showed up in particular in more acidic solution, for example, pH = 3.0, which can be explained by (6). It was also observed that corrosion in different conditions was of different forms.…”
Section: Observation and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With the increase of corrosion, hydrogen bubbles showed up in particular in more acidic solution, for example, pH = 3.0, which can be explained by (6). It was also observed that corrosion in different conditions was of different forms.…”
Section: Observation and Discussionmentioning
confidence: 88%
“…Experience and investigation of pipe failures suggest that corrosion of metals, both cast iron and steel, is the most predominant cause of pipe failures [4,5]. Since corrosion is linked to almost all pipe failures, it has become a global problem for all stakeholders, in particular engineers and asset managers of buried metal pipes [6,7]. As such, considerable research has been undertaken in the past few decades on corrosion of metal pipes, more perhaps for cast iron pipes, as represented notably by Doleac et al [8], Dean Jr. and Grab [9], O'Day et al [10], Randall-Smith et al [11], Kirmeyer et al [12], Camarinopoulos et al [13], Sadiq et al [14], Panossian et al [15], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[46,48,49] Polarization at sufficiently cathodic potentials can generate the production of OH À ions and their accumulation on the surface of the steel according to Equation (3) and (4). [15,47] The alkalization causes precipitation of weakly soluble compounds, such as CaCO 3ðsÞ , MgðOHÞ 2ðsÞ etc., [45,50] and MgCO 3ðsÞ [51] according to the following reactions…”
Section: Chronoamperometrymentioning
confidence: 99%
“…A part of perlite is arranged in the form of bands. To simulate a corrosive environment with a nearneutral pH, to which underground pipeline is exposed to, a neutral NS4 solution of the following chemical composition was used: 0,122 г/л KCl + 0,483 g/l NaHCO3 + 0,181 г/л CaCl2 + 0,131 г/л MgSO4 (рН 8,2) [12,18,[30][31][32][33]. Reagents of analytical grade and a distilled water were used.…”
Section: Materials and Test Techniquesmentioning
confidence: 99%